Dynamic Mg2B8 Cluster: A Nanoscale Compass - Wang, Ying‐Jin; Feng, Lin‐Yan; Guo, Jin‐Chang; Zhai, Hua‐Jin (Chemistry, an Asian journal, 2017)
Boron‐based binary cluster Mg2B8 is shown to adopt a compass‐like structure via computational global searches, featuring an Mg2 dimer as the needle and a disk‐shaped B8 molecular wheel as baseplate. The nanocompass has a diameter of 0.35 nm. Born–Oppenheimer molecular dynamics simulations indicate that Mg2B8 is structurally fluxional with the needle rotating freely on the baseplate, analogous to a functioning compass. The dynamics is readily initiated via a ultrasoft vibrational mode. The rotational barrier is only 0.1 kcal mol−1 at the single‐point CCSD(T) level. Chemical bonding analysis suggests that the cluster compass can be formulated as [Mg2]2+[B8]2−; that is, the baseplate and the needle are held together primarily through ionic interactions. The baseplate is doubly aromatic with π and σ sextets. The bonding pattern provides a dilute, continuous, and delocalized electron cloud, which underlies the dynamics of the nanocompass. Need some direction? Boron‐based Mg2B8 cluster assumes a nanocompass structure, with an [Mg2]2+ dimer as the needle and a [B8]2− molecular wheel as baseplate. It behaves dynamically like a compass with a near zero rotational barrier, due to delocalized electron cloud from 6 π and 6 σ double aromaticity.